Identification of Lean Six Sigma barriers in automobile part manufacturing industry. (2022) - Rathi, Rajeev; Singh, Mahipal; Kumar Verma, Alok; Singh Gurjar, Rahul; Singh, Amar; Samantha, Bijoy
Abstract: The aim of this paper is to identify the various types of barriers that an automotive component manufacturing company faces when attempting to introduce Lean Six Sigma techniques. Initially, 31 Lean Six Sigma Barrier (LSSB) were selected through an exhaustive literature review which was conducted using questionnaire survey. In the questionnaire survey, the manager's opinions were collected with the help of online emails. The collected responses were analysed through statistical tools like Importance-indexed and CIMTC. The internal consistency of the collected responses was 0.971 which is good and the outcomes of an importance index and a CIMTC analysis indicates that most of the Indian manufacturing firms were facing the challenges from LSSB-4 and LSSB-3. The identified LSSB exhibits that it is difficult to implement LSS techniques in Auto component manufacturing industries. As said above authors have researched on barriers faced by automobile industries to manufacture a unit and also going on with LSS. But, literature limited to explore the studies on parts manufacturing industries which are responsible for many unique parts of automotive units.